2004
DOI: 10.1379/csc-12r.1
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-specific association of antibodies against heat shock proteins 60 and 70 with noise-induced hearing loss in Chinese workers

Abstract: Noise exposure may result in production of auto-antibodies against heat shock proteins (Hsps), which might be of significance in the pathogenesis or prognosis (or both) of auto-immune ear diseases. However, it is not known whether these antibodies are associated with noise-induced hearing loss (NIHL) in workers exposed to noise in occupational settings. Using immunoblotting with human recombinant Hsps, audiological assessment, and multivariate logistic regression models, we investigated the presence of antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 38 publications
(39 reference statements)
1
20
1
Order By: Relevance
“…We subsequently observed that there was a significantly increased frequency of antibodies against Hsp70 (anti-Hsp70) in workers exposed to benzene, dust, heat, and noise, and that these stresses seemed to contribute to the production of an antibody against Hsp70. Interestingly, the presence of such antibodies was associated with benzene-poisoning, hypertension, noise-induced hearing loss, and abnormal changes of electrocardiography (Wu et al 1998(Wu et al , 2001bYang et al 2004b;Yuan et al 2005). Equally interesting was the observation that antibodies against Hsp70 occurred in higher titers in individuals who were more susceptible to heat-induced illness (Wang et al 2001;Wu et al 2001a).…”
Section: Association Of Anti-hsps With Environmental Stressesmentioning
confidence: 99%
See 1 more Smart Citation
“…We subsequently observed that there was a significantly increased frequency of antibodies against Hsp70 (anti-Hsp70) in workers exposed to benzene, dust, heat, and noise, and that these stresses seemed to contribute to the production of an antibody against Hsp70. Interestingly, the presence of such antibodies was associated with benzene-poisoning, hypertension, noise-induced hearing loss, and abnormal changes of electrocardiography (Wu et al 1998(Wu et al , 2001bYang et al 2004b;Yuan et al 2005). Equally interesting was the observation that antibodies against Hsp70 occurred in higher titers in individuals who were more susceptible to heat-induced illness (Wang et al 2001;Wu et al 2001a).…”
Section: Association Of Anti-hsps With Environmental Stressesmentioning
confidence: 99%
“…Moreover, another study of 27 patients with sudden deafness showed that there was no significant increase of anti-Hsp70 antibody in patients compared with controls, suggesting there was no clinical utility for diagnostic screening in this disease (Samuelsson et al 2003). Recently, Yang et al (2004b) examined the prevalence of antibodies to Hsp70 and Hsp60 in workers with noiseinduced hearing loss: antibodies to both proteins were more prevalent in such workers, but curiously anti-Hsp70 was associated with high-frequency hearing loss, whereas anti-Hsp60 was associated with moderate low-frequency loss.…”
Section: Anti-hsps In Other Diseasesmentioning
confidence: 99%
“…It is the only study that measured HSP60 itself and relate it to sensorineural hearing loss. Yang et al (2004) found that the prevalence of positive anti-HSP60 (not HSP60) in workers with moderate low-frequency NIHL was significantly higher than in normal workers (P < 0.01).…”
Section: Resultsmentioning
confidence: 84%
“…The observed intermediate cochlin autoantibody titers in the OHL cohort implies that an adaptive inner ear autoimmune response may be implicated in noiseand/or age-related hearing loss. Indeed, elevated serum Abs against other autoantigens, most notably HSP60 and HSP70, have been reported in patients with noise-induced hearing loss (36,37). Although it is appealing to consider that noise-induced inflammation may trigger pathogenic inner ear self-recognition events that lead to ASNHL, a direct link between acoustic trauma and the development of ASNHL has not been shown.…”
Section: Discussionmentioning
confidence: 99%